Implementasi Pembelian Pakaian Baru Bagi Mahasiswi Untuk Menciptakan Nilai Positif Diri Sendiri Dalam Perspektif Ekonomi Mikro Islam - Maratus, Maratus Soliha; Sari, Sheptya Mayang; Sumantri, Rinol; Iqbal, M.; Rahmani, Zikri (CV. Era Digital Nusantara, 2025)
This article discusses the implementation of purchasing new clothes for UIN Raden Fatah Palembang students as an effort to create positive values ​​within themselves. In an Islamic microeconomic perspective, purchasing clothes is not only seen from the material side, but also from the social and psychological impacts that can be caused. This research uses a qualitative approach by collecting data through interviews and surveys of female students. The research results show that purchasing new clothes can increase self-confidence, strengthen self-identity, and encourage positive social interactions. Apart from that, aspects of Islamic microeconomics which focus on justice and welfare are also an important basis for making purchasing decisions. Thus, purchasing new clothes becomes not only a necessity, but also part of an ongoing self-investment. This research is a field research that aims to explore in depth the relationship between context and interactions between individuals, groups, society and institutions. In this research, the approach used is descriptive qualitative. Purchasing new clothes for UIN Raden Fatah Palembang students not only fulfills their physical needs, but also has deeper implications for self-development, economic ethics and social relationships. By considering Islamic principles in shopping, female students can make decisions that not only benefit themselves, but also society and the environment. Therefore, it is important for female students to be aware of the impact of their choices and strive to shop in a responsible and ethical manner. awareness of budgets and expenses is very important. For example, by planning clothing purchases according to predetermined needs and budgets, female students can avoid unnecessary debt and maintain their financial health. This is in line with the principles of Islamic teachings which encourage its followers to shop wisely and not excessively.